2016
DOI: 10.1530/erc-16-0334
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane ion channels and epithelial to mesenchymal transition in cancer cells

Abstract: A variety of studies have suggested that epithelial to mesenchymal transition (EMT) may be important in the progression of cancer in patients through metastasis and/or therapeutic resistance. A number of pathways have been investigated in EMT in cancer cells. Recently, changes in plasma membrane ion channel expression as a consequence of EMT have been reported. Other studies have identified specific ion channels able to regulate aspects of EMT induction. The utility of plasma membrane ion channels as targets f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…As a primary tumour develops, the associated hypoxic environment initiates events such as the induction of a more invasive phenotype through EMT (Azimi and Monteith, 2016;Lester et al, 2007) and cell survival via autophagy (Hu et al, 2012). The studies presented here provide evidence for TRPC1 as a critical regulator of processes induced by hypoxia via HIF1α-dependent and -independent mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…As a primary tumour develops, the associated hypoxic environment initiates events such as the induction of a more invasive phenotype through EMT (Azimi and Monteith, 2016;Lester et al, 2007) and cell survival via autophagy (Hu et al, 2012). The studies presented here provide evidence for TRPC1 as a critical regulator of processes induced by hypoxia via HIF1α-dependent and -independent mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, studies have identified the remodeling of Ca 2+ signaling and/or changes in the expression of components of Ca 2+ transport as a consequence of EMT in cancer cells ( [5,[12][13][14] and reviewed in [15]). The Ca 2+ signal itself is also a key regulator of the induction of EMT by some stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical activity of pancreatic beta-cells relies on multiple types of voltage-and ligand-gated ion channels that are permeable to inorganic ions such as sodium, potassium, chloride and calcium [5], [15], [16]. These channels not only regulate membrane potential, ion homeostasis and electrical signaling [17], but a dis-regulation in their activity has been recently also implicated in tumorogenesis and tumor progression [18], [19], [20], [21].…”
Section: Single Beta-cell Models Of Bursting and Silent Dynamicsmentioning
confidence: 99%